PENGARUH GOVERNMENT FUND TERHADAP COMPREHENSIVE INCOME MONASH UNIVERSITY AUSTRALIA - Lianty, Fannyra; Christian Sardjono, Nicholas; Tiur Manurung, Elizabeth (Jurnal Akuntansi AKTIVA, 2025)
This study aims to analyze the impact of government funds on the comprehensive income of Monash University in Australia. Using documentation methods and multiple linear regression analysis, this research evaluates the university's financial data from 1992 to 2023. The results show that government funds have a significant effect on comprehensive income at a 10% significance level. Each increase in government funding by one unit contributes to a rise in comprehensive income by 0.106 units. This study highlights the importance of government funding in supporting the financial performance of universities while emphasizing the need for optimization and transparency in its utilization to achieve more effective outcomes.